Are platelet volume indices related to mortality in hospitalized children on mechanical ventilation?. Issue 3 (March 2018) - Ye, Sheng; Zhang, Yanyi; Zhang, Chenmei; Xu, Dan
Objectives: To investigate platelet volume indices and in-hospital mortality in children on mechanical ventilation. Methods: This retrospective study included children aged <16 years on mechanical ventilation, and compared parameters, measured on admission, between survivors and non-survivors. Dynamic platelet volume indices over the first 7 days were visualized. Independent risk factors of mortality were identified using multivariate logistic regression analysis. Results: Out of 2 319 children aged 28 days–3 years, serum albumin (odds ratio [OR] 0.9, 95% confidence interval [CI] 0.85, 0.96), bilirubin (OR 1.01, 95% CI 1.0, 1.77), and lactic acid (OR 1.22, 95% CI 1.05, 1.38) levels were associated with mortality. Out of 2 415 children aged > 3 years, procalcitonin (OR 1.01, 95% CI 1.0, 1.01) and lactic acid (OR 1.22, 95% CI 1.09, 1.35) were associated with mortality. Platelet volume indices on admission were not independently associated with mortality in either group. Mean platelet volume (MPV) and platelet distribution width (PDW) showed different trends in non-survivors versus survivors over 1 week in both age groups. Conclusions: Platelet volume indices may be associated with mortality in critically ill children receiving mechanical ventilation.